Physiological and cellular responses in two populations of the mussel Perna perna collected at different sites from the Coast of São Paulo, Brazil - De Souza Abessa, Denis Moledo [UNESP]; Zaroni, Letícia Pires; De Sousa, Eduinetty Ceci Pereira Moreira; Gasparro, Marcia Regina; Pereira, Camilo Dias Seabra; De Figueredo Rachid, Bauer Rodarte; Depledge, Michael; King, Rebecca Susan (FapUNIFESP (SciELO), 2005)
The physiological conditions of mussels from Ubatuba and Santos and also of organisms transplanted from Ubatuba to Santos were studied by using different techniques. Assays for lysosomal stability were conducted on the haemolymph. Heart rate activity was monitored for 6h. The embryonic development of larvae obtained from the collected mussels was analysed. For all the compared groups of mussels, no significant differences were observed for the cardiac activity monitoring and the embryonic bioassays. The mean Neutral Red (NR) retention time was similar for the animals from Santos and Ubatuba, whereas the organisms transplanted to Santos showed a reduction in the retention time of the dye, indicating damage in the lysosomal membranes. These differences were possibly due to environmental factors, but further investigations are required to confirm this hypothesis.
Keywords: Biomarkers; Capmon system; Embryonic assay; Neutral red retention assay; Perna perna; Physiology; Animalia